Try new and beautify you with 3D world of paediatric dentistry - Patil, Keyuri; GV, Babu; Bhattad, Mayur; Chandak, Ankita; Rajewar, Sumit; Patil, Sheila Konda (Journal of Neonatal Surgery, 2025)
Background / Introduction: Dental treatment of children poses significant challenges for clinicians. The conventional impression-making procedures in young children are considered cumbersome and difficult due to several clinical factors in dentistry. In recent years, digital Intra-oral sensors (IOS), three-dimensional printing (3D Printing) technology and Computer- Aided Design/Computer-Aided Manufacturing (CAD-CAM) technology have been described in existing literature related to different aspects of paediatric dentistry. Aim: To assess the knowledge, attitude and practice of the use of 3D printing technology in paediatric dentistry among post-graduate students and paediatric dentists in India. Methodology: Post-graduate students and pedodontists in India were included in this study. A survey with the google forms online tool was utilised in this study. Responses received were included for evaluation. Results: 75.2% were aware about 3D printing used specifically for pediatric dentistry, 106 (47.7%) participants wanted to know more regarding 3D printing through live demonstrations. A statistically insignificant difference was found in the knowledge and practices based on gender, education, and experience with P value ≤ 0.05. Conclusion: Through survey we found that although post-graduate students and pediatric dentists in India showed enough understanding, had positive attitude about 3D printing, just a few percent of them were unable to successfully incorporate this technology into their routines